Mixed-Income Housing Strategy in Urban Renewal Policies and Turkey-Specific Dynamics: Altindag-Gultepe Case, Ankara - Bektas, Yasin; Turkun, Asuman (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
One of the important changes in both public housing areas and national urban renewal policies of North America and Western European countries in the 1990s is the Mixed-Income Housing Strategy. It is grounded on the assumption that problems of poverty will be solved more easily and society will function more efficiently if the society is mixed in terms of society and economy and if suitable spatial organization are made and necessary public services provided. The problems related to transformations only in physical terms have led to a more comprehensive and long-term approach in urban transformation considering parameters such as sustainability, diversity and participation. In Turkey, the current policy concerning particularly the housing areas of low-income groups constitutes demolishing the existing buildings and moving the titleholders to housing blocks built generally by Mass Housing Development Agency (TOKI) in the same area or on the periphery of the city. Apart from the titleholders from demolished areas, the new flats are sold to households with a range of income levels. Hence, outcomes similar to those emerging from mixed-housing areas in western countries can be observed in these areas. However, this situation does not stem from a decisive policy of minimizing the negative effects of poverty concentration but from a similarity in practice. In this article, the housing policies of both developed western countries and Turkey, especially after the 1980s, will be explored. Based on the doctoral thesis, a case study was created between 2012 and 2015 on Gultepe Squatter Renewal Area in Altindag district, the first and most important squatter housing area of Ankara. Based on the findings of the case study, the social, economic, and spatial results of urban renewal practices in squatter housing areas as well as the contingent developments similar to mixed-income housing areas will be discussed.
Keywords: Squatter housing; mixed-income housing; urban regeneration; social interaction; social mix; MIDDLE-CLASS; GENTRIFICATION; RENAISSANCE; Architecture